Handbook for Venous Thromboembolism - Piazza, Gregory. (Springer International Publishing : Imprint: Springer, 2015)
This handbook provides a state-of-the-art but practical guide to understanding the risk factors and pathophysiology, diagnosis and risk stratification, and treatment and prevention of venous thromboembolism (VTE). VTE, including deep vein thrombosis and pulmonary embolism , is the third most common cardiovascular disorder after myocardial infarction and stroke. Accordingly, an understanding of the risk factors, pathophysiology, diagnosis, treatment, and prevention of VTE is critical for all clinicians, and not just cardiovascular medicine specialists. With the use of clinical vignettes and self-assessment questions to emphasize key concepts from each chapter, Handbook of Venous Thromboembolism will enable readers to incorporate changes in a rapidly advancing field into the daily care of patients who have suffered or are at risk of developing VTE.